In mathematics, specifically differential calculus, the inverse function theorem gives a sufficient condition for a function to be invertible in a neighborhood of a point in its domain: namely, that its derivative is continuous and non-zero at the point. The theorem also gives a formula for the derivative of the inverse function.In multivariable calculus, this theorem can be generalized to any continuously differentiable, vector-valued function whose Jacobian determinant is nonzero at a point in its domain, giving a formula for the Jacobian matrix of the inverse. There are also versions of the inverse function theorem for holomorphic functions, for differentiable maps between manifolds, for differentiable functions between Banach spaces, and so forth.
The theorem was first established by Picard and Goursat using an iterative scheme: the basic idea is to prove a fixed point theorem using the contraction mapping theorem.
For functions of a single variable, the theorem states that if
f
a
f
a
b=f(a)
b
f
a
It can happen that a function
f
a
f'(a)=0
f(x)=(x-a)3
b=f(a)
f-1
b
1=(f-1\circf)'(a)=(f-1)'(b)f'(a)
f'(a)\ne0
For functions of more than one variable, the theorem states that if
f
A
Rn
\Rn
f'(a)
U
a
A
V
b=f(a)
f(U)\subsetV
f:U\toV
f=(f1,\ldots,fn)
yi=fi(x1,...,xn)
x1,...,xn
y1,...,yn
x\inU,y\inV
f
f'
f'
Moreover, the theorem says that the inverse function
f-1:V\toU
b=f(a)
f'(a)
(f-1)'(b)=f'(a)-1.
Jf-1(b),Jf(a)
(f-1)'(b),f'(a)
Jf-1(b)=Jf(a)-1.
f-1
f-1\circf=I
1=I'(a)=(f-1\circf)'(a)=(f-1)'(b)\circf'(a).
f
k
k
k
infty
There are two variants of the inverse function theorem. Given a continuously differentiable map
f:U\toRm
f'(a)
m
g
V
b=f(a)
f\circg=I
b
f'(a)
g
V
b=f(a)
g\circf=I
a
In the first case (when
f'(a)
b=f(a)
m=\dim\ker(f'(a))+\dim\operatorname{im}(f'(a))
b=f(a)
a
a
f'(a)
These variants are restatements of the inverse functions theorem. Indeed, in the first case when
f'(a)
T
f'(a)\circT=I
h(x)=a+Tx
(f\circh)'(0)=f'(a)\circT=I.
f\circh
0
f\circh\circ(f\circh)-1=I
b
f'(a)
F:R2\toR2
F(x,y)= \begin{bmatrix} {ex\cosy}\\ {ex\siny}\\ \end{bmatrix}.
(x,y)
JF(x,y)= \begin{bmatrix} {ex\cosy}&{-ex\siny}\\ {ex\siny}&{ex\cosy}\\ \end{bmatrix}
\detJF(x,y)= e2x\cos2y+e2x\sin2y= e2x.
The determinant
e2x
R2
F(x,y)=F(x,y+2\pi)
If one drops the assumption that the derivative is continuous, the function no longer need be invertible. For example
f(x)=x+2x2\sin(\tfrac1x)
f(0)=0
f'(x)=1-2\cos(\tfrac1x)+4x\sin(\tfrac1x)
f'(0)=1
x=0
f
f
x=0
f'(0)=1
As an important result, the inverse function theorem has been given numerous proofs. The proof most commonly seen in textbooks relies on the contraction mapping principle, also known as the Banach fixed-point theorem (which can also be used as the key step in the proof of existence and uniqueness of solutions to ordinary differential equations).[2] [3]
Since the fixed point theorem applies in infinite-dimensional (Banach space) settings, this proof generalizes immediately to the infinite-dimensional version of the inverse function theorem[4] (see Generalizations below).
An alternate proof in finite dimensions hinges on the extreme value theorem for functions on a compact set. This approach has an advantage that the proof generalizes to a situation where there is no Cauchy completeness (see).
Yet another proof uses Newton's method, which has the advantage of providing an effective version of the theorem: bounds on the derivative of the function imply an estimate of the size of the neighborhood on which the function is invertible.[5]
We want to prove the following: Let
D\subseteq\R
x0\inD,f:D\to\R
D
f'(x0)\ne0
I
x0\inI
f
I
J=f(I)
f-1:J\toI
y\inJ
x\inI
f(x)=y
(f-1)'(y)=\dfrac{1}{f'(x)}
We may without loss of generality assume that
f'(x0)>0
D
f'
x0
r>0
(x0-r,x0+r)\subseteqD
In particular,
This shows that
f
|x-x0|<r
\delta>0
\delta<r
[x-\delta,x+\delta]\subseteq(x0-r,x0+r)
f
[x-\delta,x+\delta]
[f(x-\delta),f(x+\delta)]
I=(x-\delta,x+\delta)
J=(f(x-\delta),f(x+\delta))
f:I\toJ
f-1:J\toI
f-1:J\toI
f
f:I\to\R
x0\inI
f'(x0)\ne0
f-1:f(I)\to\R
(f-1)'(y0)=\dfrac{1}{f'(y0)}
y0=f(x0)
To prove existence, it can be assumed after an affine transformation that
f(0)=0
f\prime(0)=I
a=b=0
By the mean value theorem for vector-valued functions, for a differentiable function
u:[0,1]\toRm
u(t)=f(x+t(x\prime-x))-x-t(x\prime-x)
\|f(x)-f(x\prime)-x+x\prime\|\le\|x
\prime\|\sup | |
-x | |
0\let\le1 |
\|f\prime(x+t(x\prime-x))-I\|.
Now choose
\delta>0
\|x\|<\delta
\|y\|<\delta/2
xn
x0=0
xn+1=xn+y-f(xn)
\|x\|,\|x\prime\|<\delta
\|f(x)-f(x\prime)-x+x\prime\|\le\|x-x\prime\|/2
In particular
f(x)=f(x\prime)
x=x\prime
\|xn\|<\delta
\|xn+1-xn\|<\delta/2n
(xn)
x
f(x)=y
To check that
g=f-1
g(y+k)=x+h
f(x+h)=f(x)+k
\|h-k\|<\|h\|/2
\|h\|/2<\|k\|<2\|h\|
A=f\prime(x)
\|A-I\|<1/2
B=I-A
\|A-1\|<2
{\|g(y+k)-g(y)-f\prime(g(y))-1k\|\over\|k\|}={\|h-f\prime(x)-1[f(x+h)-f(x)]\|\over\|k\|}\le4{\|f(x+h)-f(x)-f\prime(x)h\|\over\|h\|}
tends to 0 as
k
h
g
g\prime(y)=f\prime(g(y))-1
The proof above is presented for a finite-dimensional space, but applies equally well for Banach spaces. If an invertible function
f
k>1
F(A)=A-1
k
Here is a proof based on the contraction mapping theorem. Specifically, following T. Tao,[7] it uses the following consequence of the contraction mapping theorem.
Basically, the lemma says that a small perturbation of the identity map by a contraction map is injective and preserves a ball in some sense. Assuming the lemma for a moment, we prove the theorem first. As in the above proof, it is enough to prove the special case when
a=0,b=f(a)=0
f'(0)=I
g=f-I
t\mapstog(x+t(y-x))
|g(y)-g(x)|\le|y-x|\sup0|g'(x+t(y-x))|.
g'(0)=I-I=0
g'
r>0
|g(y)-g(x)|\le2-1|y-x|
x,y
B(0,r)
f=g+I
B(0,r)
B(0,r/2)\subsetf(B(0,r))
f:U=B(0,r)\capf-1(B(0,r/2))\toV=B(0,r/2)
f-1
g=f-1
f
A=f'(x)
x=g(y)
g(y+k)=x+h
y+k=f(x+h)
|h-k|=|f(x+h)-f(x)-h|\le|h|/2
|h|/2\le|k|
\| ⋅ \|
|g(y+k)-g(y)-A-1k|=|h-A-1(f(x+h)-f(x))|\le\|A-1\||Ah-f(x+h)+f(x)|.
k\to0
h\to0
|h|/|k|
g
y
g'(y)=f'(g(y))-1
g'
\iota\circf'\circg
\iota:T\mapstoT-1
g'
It remains to show the lemma. First, we have:
|x-y|-|f(x)-f(y)|\le|g(x)-g(y)|\lec|x-y|,
(1-c)|x-y|\le|f(x)-f(y)|.
f(B(0,r))\supsetB(0,(1-c)r)
y
B(0,(1-c)r)
F:\overline{B}(0,r')\to\overline{B}(0,r'),x\mapstoy-g(x)
0<r'<r
|y|\le(1-c)r'
F
f(B(0,r))\subsetB(0,(1+c)r)
|f(x)|=|x+g(x)-g(0)|\le(1+c)|x|.\square
As might be clear, this proof is not substantially different from the previous one, as the proof of the contraction mapping theorem is by successive approximation.
The inverse function theorem can be used to solve a system of equations
\begin{align} &f1(x)=y1\\ & \vdots\\ &fn(x)=yn,\end{align}
y1,...,yn
x=(x1,...,xn)
\begin{align} &f1(x,y)=0\\ & \vdots\\ &fn(x,y)=0\end{align}
y
x
f:Rn x Rm\toRm
f(a,b)=0
f
(a,b)
y\mapstof(a,y)
b
g:U\toV
U,V
a,b
f(x,g(x))=0
f(x,y)=0,x\inU,y\inV
y=g(x)
g(x)
F(x,y)=(x,f(x,y))
F:U x V\toW
G
U,V,W
(x,y)=F(G1(x,y),G2(x,y))=(G1(x,y),f(G1(x,y),G2(x,y))),
x=G1(x,y)
y=f(x,G2(x,y)).
g(x)=G2(x,0)
\square
In differential geometry, the inverse function theorem is used to show that the pre-image of a regular value under a smooth map is a manifold. Indeed, let
f:U\toRr
Rn
a
f-1(b)
Rn
\left[
\partialfi | |
\partialxj |
(a)\right]1
r
F:U\toRr x Rn-r=Rn,x\mapsto(f(x),xr+1,...,xn)
F'(a)
n
G
F
V x W
(b,ar+1,...,an)
x=(F\circG)(x)=(f(G(x)),Gr+1(x),...,Gn(x)),
(f\circG)(x1,...,xn)=(x1,...,xr).
G
f
G:V x W\toU'=G(V x W)
g=G(b, ⋅ ):W\tof-1(b)\capU',(xr+1,...,xn)\mapstoG(b,xr+1,...,xn)
g
f-1(b)
a
f-1(b)
\square
More generally, the theorem shows that if a smooth map
f:P\toE
M\subsetE
f-1(M)\hookrightarrowP
The inverse function theorem is a local result; it applies to each point. A priori, the theorem thus only shows the function
f
Proof:[9] First assume
X
xi\neyi
f(xi)=f(yi)
xi,yi
x,y
A
f
A
x=y
i
xi,yi
x=y
f
xi=yi
In general, consider the set
E=\{(x,y)\inX2\midx\ney,f(x)=f(y)\}
S x S
S\subsetX
f
X1\subsetX2\subset …
X
Xi
Xi+1
i
Ui
A\capXi
2 | |
U | |
i |
\subsetX2-E
U=cupiUi
\square
The lemma implies the following (a sort of) global version of the inverse function theorem:
Note that if
A
There is a version of the inverse function theorem for holomorphic maps.
The theorem follows from the usual inverse function theorem. Indeed, let
JR(f)
f
xi,yi
J(f)
zj,\overline{z}j
\detJR(f)=|\detJ(f)|2
f
0
w=f(z)
\partial | |
\partial\overline{z |
j}
-1 | |
(f | |
j |
\circf)(z)=\sumk
| |||||||||
\partialwk |
(w)
\partialfk | |
\partial\overline{z |
j}(z)+\sumk
| |||||||||
\partial\overline{w |
k}(w)
\partial\overline{f | |
k}{\partial |
\overline{z}j}(z)
-1 | |
f | |
j |
\circf
fk
| |||||||||
\partial\overline{w |
k}(w)=0
k
\square
Similarly, there is the implicit function theorem for holomorphic functions.
As already noted earlier, it can happen that an injective smooth function has the inverse that is not smooth (e.g.,
f(x)=x3
The inverse function theorem can be rephrased in terms of differentiable maps between differentiable manifolds. In this context the theorem states that for a differentiable map
F:M\toN
C1
F
dFp:TpM\toTF(p)N
p
M
U
p
F|U:U\toF(U)
is a diffeomorphism. Note that this implies that the connected components of and containing p and F(p) have the same dimension, as is already directly implied from the assumption that dFp is an isomorphism.If the derivative of is an isomorphism at all points in then the map is a local diffeomorphism.
The inverse function theorem can also be generalized to differentiable maps between Banach spaces and .[11] Let be an open neighbourhood of the origin in and
F:U\toY
dF0:X\toY
F(0)
G:V\toX
F(G(y))=y
G(y)
F(x)=y
There is also the inverse function theorem for Banach manifolds.[12]
The inverse function theorem (and the implicit function theorem) can be seen as a special case of the constant rank theorem, which states that a smooth map with constant rank near a point can be put in a particular normal form near that point.[13] Specifically, if
F:M\toN
p\inM
F(p)
u:TpM\toU
v:TF(p)N\toV
F(U)\subseteqV
dFp:TpM\toTF(p)N
v-1\circF\circu
p\inM
p
When the derivative of is injective (resp. surjective) at a point, it is also injective (resp. surjective) in a neighborhood of, and hence the rank of is constant on that neighborhood, and the constant rank theorem applies.
If it is true, the Jacobian conjecture would be a variant of the inverse function theorem for polynomials. It states that if a vector-valued polynomial function has a Jacobian determinant that is an invertible polynomial (that is a nonzero constant), then it has an inverse that is also a polynomial function. It is unknown whether this is true or false, even in the case of two variables. This is a major open problem in the theory of polynomials.
When
f:Rn\toRm
m\leqn
f
k
A=\nablaf(\overline{x})
\overline{x}
m
f
s
f(s(y))=y
y
\overline{y}=f(\overline{x})
s(\overline{y})=\overline{x}
s
k
\nablas(\overline{y})=AT(AAT)-1
\nablas(\overline{y})
A
The inverse function theorem also holds over a real closed field k (or an O-minimal structure).[15] Precisely, the theorem holds for a semialgebraic (or definable) map between open subsets of
kn
The usual proof of the IFT uses Banach's fixed point theorem, which relies on the Cauchy completeness. That part of the argument is replaced by the use of the extreme value theorem, which does not need completeness. Explicitly, in, the Cauchy completeness is used only to establish the inclusion
B(0,r/2)\subsetf(B(0,r))
B(0,r/4)\subsetf(B(0,r))
y
B(0,r/4)
P(x)=|f(x)-y|2
\overline{B}(0,r)
P'(x)=0
0=P'(x)=2[f1(x)-y1 … fn(x)-yn]f'(x)
f(x)=y
f'(x)
P
x0
\overline{B}(0,r)
B(0,r)
2-1|x|\le|f(x)|
P'(x0)=0
f(x0)=y
\square
. 10.1017/CBO9780511525919. Tame Topology and O-minimal Structures. London Mathematical Society lecture note series, no. 248. 1998 . Dries . L. P. D. van den . Lou van den Dries. 9780521598385. Cambridge University Press. Cambridge, New York, and Oakleigh, Victoria .